Implementasi Kebijakan Mitigasi Bencana Banjir Pada Badan Penanggulangan Bencana Daerah Kota Tangerang Selatan - Cintya Febrianti Nuraini; Abdul Rahman (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
South Tangerang City is one of the areas prone to flooding, with various influencing factors, such as a lack of communication between local government organizations and weak spatial planning supervision. Uncontrolled development by several large developers has constricted river flows, while suboptimal drainage and water absorption systems have exacerbated the situation. In flood mitigation efforts, coordination between the Regional Disaster Management Agency, the Public Works Agency and the Environment Agency is necessary to ensure anticipatory efforts and sustainable solutions. Existing Regional Regulations and Governor Regulations, including regional spatial plans and technical guidelines for flood control, are an important foundation for flood management in the region. The purpose of this research is to find out and analyze how the implementation of flood disaster mitigation policies in Regional Regulation Number 2 of 2012 concerning Disaster Management. This research uses the theory of George C. Edward III. with 4 indicators, namely communication, resources, disposition, and bureaucratic structure. The results showed that the unity of action in handling floods still faced obstacles, where the Environmental Agency had not fully carried out its responsibilities in maintaining waste in drainage channels and rivers.